A study of 3D printed active carbon electrode for the manufacture of electric double-layer capacitors. (January 2017) - Areir, Milad; Xu, Yanmeng; Zhang, Ruirong; Harrison, David; Fyson, John; Pei, Eujin
Abstract: This paper reports an experimental investigation of the potential for printing selected commercially available activated carbon (AC) onto a flexible fabric. A dual nozzle deposition system was used based on fused deposition modelling (FDM) solid-based process. This is capable of extruding an AC slurry for making Electric Double-Layer Capacitors (EDLCs). We used an adaptive slicing approach which allows us to modify the layer thickness and deposit a controlled amount of AC materials with an accurate orientation to form predetermined tracks. Several forms of AC slurry were difficult to deposit because of the carbon particle size and acid concentration. This work discusses how the supercapacitor behaves in relation to the printed AC layers. The effects of the fabrication processes on the AC electrodes were further investigated. FDM/Paste material deposition could provide a method for making several functional elements in one process, for example printing piezoelectric materials and energy storage for smart products. The major contribution of this work is an approach for printing multilayer AC as electrodes by using 3D printing technology. The 3D printing technology allows the manufacture of complex internal patterns accurately, and provides the ability to build various thicknesses of layers in a fast and smooth operation.